2022
DOI: 10.1002/srin.202200358
|View full text |Cite
|
Sign up to set email alerts
|

Hot Deformation Behavior and 3D Processing Maps of Mn18Cr18N Steel

Abstract: The isothermal hot deformation behavior in the ranges of 1023–1473 K (750–1200 °C) and 0.001–10 s−1 for 0.53 wt% N‐bearing Mn18Cr18N steel is studied with a Gleeble‐3500 thermomechanical simulator. The results indicate that the peak stress decreases with decreasing strain rate and increasing temperature. The calculated deformation activation energy of the experimental steel is 449.118 kJ mol−1 by regression analysis. At the same time, 3D processing maps are established based on experimental data and the princi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Generally, the relationship between flow stress and strain rate can be described by Equation (6). [ 52,53 ] σ=Ktrueε.mwhere K is the material constant, and m is the strain rate sensitivity coefficient. According to Equation (6), the strain rate sensitivity coefficient can be calculated by Equation (7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the relationship between flow stress and strain rate can be described by Equation (6). [ 52,53 ] σ=Ktrueε.mwhere K is the material constant, and m is the strain rate sensitivity coefficient. According to Equation (6), the strain rate sensitivity coefficient can be calculated by Equation (7).…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the relationship between flow stress and strain rate can be described by Equation ( 6). [52,53] σ ¼ Kε…”
Section: Analysis Of Strain Rate Sensitivitymentioning
confidence: 99%
“…Xi et al [ 17 ] studied instability of 317LN‐Cu medical stainless steel during processing, the processing maps were established based on the DMM to predict the suitable hot processing interval. Zhang et al [ 18 ] examined the deformation behavior of Mn18Cr18N steel. It was observed that the DRX would progressively rise as the deformation temperature increased, and an increase in strain rate was identified as result in a significant reduction in both the DRX grain size and DRX fraction.…”
Section: Introductionmentioning
confidence: 99%